Perioperative and oncologic outcome in patients treated for renal cell carcinoma with an extended inferior vena cava tumour thrombus level II-IV - Ralla, Bernhard; Adams, Lisa; Maxeiner, Andreas; Mang, Josef; Krimphove, Michael; Dushe, Simon; Makowski, Marcus; Miller, Kurt; Fuller, Florian; Busch, Jonas (Aktuelle Urologie, 2019)
Purpose Surgical treatment of patients with renal cell carcinoma (RCC) and an extended tumour thrombus (TT) in the inferior vena cava (IVC) is challenging and often requires a multidisciplinary approach. The aim of this study was to analyse results in the real-world management of RCC patients with an extended IVC TT (level II-IV according to the Mayo classification of macroscopic venous invasion in RCC) in terms of pre-, peri- and postoperative outcome, complications and oncologic outcome. Methods We investigated 61 patients with evidence of RCC and an extended TT in the IVC undergoing radical nephrectomy and tumour thrombectomy at our tertiary referral centre. Patients and operative characteristics were recorded and complications were analysed using the Clavien-Dindo classification. Follow-up data were retrieved by contacting the treating outpatient urologists, general practitioners and patients. Results The TT level was II in 36, III in 8 and IV in 17 patients. Complications grade IIIb and higher according to the Clavien-Dindo classification occurred in n = 3 (8.4 %), n = 2 (25.0 %) and n = 5 (29.5 %) patients with level II, III and IV TT, respectively. The overall survival of patients with TT level II, III and IV at 24 months (60 months) was 66.9 % (41.6 %), 83.3 % (83.3 %) and 64.1 % (51.3 %). Presence of primary metastatic disease was the only significant independent predictor for OS. Conclusions Radical nephrectomy with tumour thrombectomy appears to be a feasible and effective treatment option in the management of patients with RCC and an extended IVC TT.
Keywords: RCC; renal cell carcinoma; IVC; inferior vena cava; tumour thrombus